Pengaruh Pendekatan Matematika Realistik (PMR) Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa Kelas X Mas NU Sibuhuan - Sundut Azhari Hasibuan; Asni Adawiyah Hasibuan (Journal of Information System and Education Development, 2024)
Mathematics is one of the lessons with a structured, systematic learning pattern and closely related to facts, concepts, and problem solving procedures. In general, at MAS NU Sibuhuan school, in the process of learning mathematics, teachers still rely on the lecture method which results in learning that focuses on the process. This results in low comprehension of mathematical concepts. To overcome this, teachers should use appropriate learning models, therefore researchers use the PMR model. This study aims to determine whether there is an influence of the PMR to improve the ability to understand mathematical concepts of grade X students of MAS NU Sibuhuan. The type of research used is quantitative research with quasi-experimental research methods with Prettest-Posttest Only Control Group Design research design. This study had two sample groups, namely experimental classes with PMR learning models and control classes with conventional learning models. The research data were analyzed using the Mann Whitney test. From the results of the study, it can be seen that based on the hypothesis testing criteria with a significant level of ? = 0.05 testing criteria, a significant 0.000 < 0.05 was obtained. Based on its decision-making criteria, H0 is accepted. So, there is an influence of a realistic mathematical approach to improve the ability to understand mathematical concepts of grade X students of MAS NU Sibuhuan.